THE CLIMATE EFFECTS ON POSIDONIA OCEANICA AND ITS ASSOCIATED FAUNA - Katiuscia Petrosillo; Gianluca Sara; Cinzia De Vittor; Valentina Esposito
Posidonia oceanica is a habitat former and an endemic species of the Mediterranean Sea, where it forms extensive meadows in the infralittoral zone, representing one of the most important coastal ecosystems, playing key roles in biodiversity conservation as it serves as a nursery and shelter for many animals and algae1. So, it is important to investigate the multifaceted effects of climate stressors on its ecological structure, physiology and productivity to preserve this important keystone species. In particular, experiments conducted in volcanic coastal areas, where CO2 naturally leaks from the seafloor, show that P. oceanica can benefit from elevated CO2 concentrations and thrive under conditions of ocean acidification (OA) predicted by the IPCC panel for the next century2. One of the widest shallow hydrothermal systems in Italy is located in the Aeolian archipelago, off the Panarea island, hosting settlements of P. oceanica, characterized by unique plant features, such as reduced plant size, lack of a seasonal growth cycle, and a poor epiphytic leaf community3. To deep know the effects of Marine Heat Waves (MHW) and hypersalinity on these acidified meadows, multiple stressors exposure mesocosms will be performed with acidified Posidonia sampled in Panarea, with the intent to identify responses to multiple stressors of Posidonia exposed for long periods to high quantity of CO2 and biological traits useful to compare the conservation status of Posidonia meadows in the Mediterranean Sea to preserve them and all the biodiversity associated with them.